Effect of maternal weight on fetal outcome - Ushadevi Gopalan; Arul Anne Rose S (International Journal of Medical Research and Review, 2015)
Introduction: Pregnancy in chronically undernourished women with low maternal weight results in delivery of low birth weight babies.Aim of the Study: our aim was to study the correlation between maternal weight during pregnancy with fetal outcome measured in terms of fetal weight and perinatal mortality.Materials and Methods: This was a hospital based prospective study conducted in the department of obstetrics and gynecology in our teaching medical college and hospital over a period of 2 years extending from Jan 2011 - Dec 2012. All the cases delivering in this hospital were taken for this study. Total of about 1449 cases were taken for this study.Results: In this study the average weight of patients was found to be 51.88±7.64 kg. The mean birth weight was found to increase with increasing maternal weight. The difference in the mean birth weight was found to be statistically significant between the different groups (P<0.01) except between those patients with weight in range of 50-60 and those above 61 kg (P>0.05).There was found to be a statistically significant increase in birth weight with increase in maternal third trimester weight from less than 45 kg to 55 kg. Differences in perinatal mortality between these groups were found to be statistically insignificant (P>0.05).Conclusion: There was statistically significant increase in mean birth weight with increase in maternal weight upto 60 kg. There was no correlation between perinatal mortality rate and maternal weight.